2016
DOI: 10.1063/1.4948729
|View full text |Cite
|
Sign up to set email alerts
|

Thermophoretically induced large-scale deformations around microscopic heat centers

Abstract: Selectively heating a microscopic colloidal particle embedded in a soft elastic matrix is a situation of high practical relevance. For instance, during hyperthermic cancer treatment, cell tissue surrounding heated magnetic colloidal particles is destroyed. Experiments on soft elastic polymeric matrices suggest a very long-ranged, non-decaying radial component of the thermophoretically induced displacement fields around the microscopic heat centers. We theoretically confirm this conjecture using a macroscopic h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…5, A co and A in in general cannot be obtained from coarse-grained macroscopic velocity fields v co and v in . Establishing corresponding two-or three-fluid hydrodynamic descriptions [51,[60][61][62] for (visco)elastic composite materials will be an interesting subject for the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, A co and A in in general cannot be obtained from coarse-grained macroscopic velocity fields v co and v in . Establishing corresponding two-or three-fluid hydrodynamic descriptions [51,[60][61][62] for (visco)elastic composite materials will be an interesting subject for the future.…”
Section: Discussionmentioning
confidence: 99%
“…In this expression, the coefficients κ ij are related to heat conduction [9], D ij and D (T ) ij describe diffusion and thermodiffusion [9,[56][57][58][59][60], respectively, while ν ijkl comprise the viscosities [9]. Next, the coefficients ζ x ijkl include irreversible relaxation processes of strains [51,61], e.g.…”
Section: B Dissipative Dynamicsmentioning
confidence: 99%
“…In the final step, another layer of PDMS (of the same composition) was poured over the first, which was cured for another 24 h at 60 • C. Thus, the particles are fully encapsulated by the matrix material (Fig. 1 b) and figure 3 in [26]. As dimensions of the final PDMS gels exceed the particle diameters (and their typical displacements) by a factor of ≈ 10, the influence of the boundaries on the particle motion can be neglected.…”
Section: Methodsmentioning
confidence: 99%
“…In samples similar to the ones studied here, it has been shown that non-local matrix-mediated interactions can be described in an iterative procedure inspired by the Oseentensor formalism in hydrodynamics [26]. Here, the system is described as an interplay between mutual magnetic forces and the opposing elastic matrix deformations caused by particle displacement.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation